Personality traits and social frailty in older adults: exploring the mediating effect of perceived loneliness - Sardella, Alberto; Lenzo, Vittorio; Razza, Grazia; Maci, Tiziana; Russo, Samuele; Cannavò, Dario; Caponnetto, Pasquale; Basile, Giorgio; Quattropani, Maria C. (Frontiers in Public Health, 2025)
IntroductionThe relationship between personality traits, as defined by the Five Factor Model (FFM), and social frailty—according to the Gobbens model—represents a relatively novel area of research. Moreover, few studies have examined the link between personality and loneliness, a key determinant of social frailty, in older adults. This study aimed to explore the association between FFM personality traits and social frailty, and to assess whether perceived loneliness mediates this relationship.MethodsThis cross-sectional observational study involved community-dwelling older adults attending a Geriatric Outpatients Clinic. Individuals aged ≥65 years were enrolled; those with diagnosed major neurocognitive disorders or psychiatric conditions were excluded. Personality traits were assessed using the Ten-Item Personality Inventory (TIPI), loneliness via the UCLA Loneliness Scale, and frailty through the Tilburg Frailty Indicator (TFI).ResultsData from 202 participants were analyzed (mean age: 74.45 ± 7.76 years; 57% female). Neuroticism was the only trait significantly associated with perceived loneliness (r = 0.190; p = 0.007). Perceived loneliness, in turn, was the sole variable significantly associated with social frailty (r = 0.526; p < 0.001). A mediation model (with age as covariate) revealed that loneliness fully mediated the relationship between Neuroticism and social frailty: the completely standardized indirect effect [β = 0.1017; 95% CI (0.0376, 0.1714)] confirms a moderate mediation effect.ConclusionsIn older adults, higher levels of Neuroticism—reflecting a tendency toward negative affectivity—are linked to increased social frailty, primarily through the mediating role of perceived loneliness.